Metode Penurunan Persentase Lemak Pada Daerah Tubuh Tertentu Melalui Aplikasi Latihan Workout - Widi Kusumah; Yudi Nurcahya (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
One of the most important factors in the world of fitness is how to lose fat in the body. Exercise using applications is one method that is believed by the general public to be useful for losing fat in one part of the body, but the clarity of the effect of this exercise on reducing fat percentage has not been clearly revealed. Therefore, it is important to do research on this problem. The purpose of this study was to determine the impact of exercise using the application on decreasing the percentage of fat. This study used an experimental method. The population used in this study were elementary school students who were classified as obese using purposive sampling technique, and were divided into two groups by ranking. Based on data processing, the authors draw the following conclusions: Abdominal exercises have a significant impact on reducing the percentage of fat in the abdominal area. As a control group, conventional exercise also had a significant effect on reducing the percentage of fat in the abdominal area.